iPack: in-Network Packet Mixing for High Throughput Wireless Mesh Networks - Alimi, Richard; Li, Li Erran; Ramjee, Ramachandran; Viswanathan, Harish; Yang, Yang Richard (IEEE Infocom, 2008)
A major barrier for the adoption of wireless mesh networks is severe limits on throughput. Many in-network packet mixing techniques at the network layer [1], [2], [3] as well as the physical layer [4], [5], [6] have been shown to substantially improve throughput. However, the optimal mixing algorithm that maximizes throughput is still unknown. In this paper, we propose iP ack, an algorithm for in-network generation of composite packets that integrates coding at two different layers of the protocol stack: XOR-based network coding and physical layer superposition coding. Using extensive simulations, we find that the throughput gain of the joint coding iP ack algorithm is 30% more than the better performer of network coding and superposition coding in a wide range of scenarios, and automatically takes advantage of the best available coding opportunities. In a typical wireless mesh network when more traffic is between the clients and access points, the average throughput improvement of iP ack, our joint optimization scheduler, can be 324%, while there can be little gain (less than 10%) if network coding alone is used. We also validate our results by implementing iP ack on a small-scale testbed based on GNU Radio.